Biohybrid bacterial microswimmers with metal-organic framework exoskeletons enable cytoprotection and active drug delivery in a harsh environment. (March 2022) - Li, Y.; Tang, S.; Cong, Z.; Lu, D.; Yang, Q.; Chen, Q.; Zhang, X.; Wu, S.
Abstract: The inspiring idea of using motile bacteria as bioengines to create biohybrid microswimmers has been realized by integrating functionalized cargos with bacteria recently. However, existing pernicious factors in ambient conditions, such as enzymes, may attack bacterial microsystems when they are executing tasks. Here, a versatile bacterial microswimmer system with cytoprotective metal-organic framework (MOF) exoskeletons is reported, capable of protecting the bioengine from enzyme degradation. Zeolitic imidazolate framework-8 (ZIF-8) nanoparticles (NPs) are fully coated on the surface of motile bacteria ( Escherichia coli MG1655 ) through tannic acid (TA) complexation. The ZIF-8 wrapping is demonstrated with negligible influence on bacterial motility under optimized conditions. Moreover, ZIF-8@ E. coli microswimmers still maintain their shapes and motion performance in the presence of lysozyme, verifying the effective preservation of formed ZIF-8 exoskeletons on the bacterial surface. Coupling with the drug loading capacity of ZIF-8, Doxorubicin (DOX)-loaded ZIF-8@ E. coli microsystems retain their effective propulsion after being treated with lysozyme, enabling the accelerated crossing through the Transwell membrane and improving anticancer efficacy compared with passive drugs. The fabricated bacterial microswimmers were also verified with chemotactic motion and prolonged retention time in the mouse bladder, holding great potential to design an active medical platform with improved therapeutic efficacy for targeted disease treatment, such as bladder cancer. Combining bacteria with MOFs generates multifunctional biohybrid microswimmers with capabilities of cytoprotection and active drug delivery. Such design facilitates the development of active biosystems to apply in harsh environments and meets rigorous requirements in clinical biomedical applications. Highlights: A versatile bacterial microswimmer is presented by encapsulating bacteria with ZIF-8 nanoparticles. The ZIF-8 wrapping has negligible influence on bacterial viability and motility. The porous ZIF-8 exoskeletons protect the bacterial engine from lysozyme degradation. The fabricated bacterial microswimmers are capable of active and chemotaxis-induced targeted drug delivery. Such design eliminates the major barrier that apply bacterial microswimmers in practical environments with biothreats.